2011
DOI: 10.1038/nclimate1327
|View full text |Cite
|
Sign up to set email alerts
|

Lack of uniform trends but increasing spatial variability in observed Indian rainfall extremes

Abstract: Recent studies disagree on how rainfall extremes over India have changed in space and time over the past half century 1-4 , as well as on whether the changes observed are due to global warming 5,6 or regional urbanization 7 . Although a uniform and consistent decrease in moderate rainfall has been reported 1,3 , a lack of agreement about trends in heavy rainfall may be due in part to differences in the characterization and spatial averaging of extremes. Here we use extreme value theory [8][9][10][11][12][13][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
213
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(229 citation statements)
references
References 29 publications
11
213
3
2
Order By: Relevance
“…They have reported that in spite of considerable year-to-year variability, there are significant increases in the frequency and the intensity of extreme monsoon rain events in central India over the past 50 years and the observed trends suggest enhanced risks associated with extreme rainfall over India in the coming decades. The findings of Ghosh et al 23,24 were similar to those of Goswami et al 19 . Lacombe and McCartney 25 found changes in rainfall pattern aligning with the geography of anthropogenic atmospheric disturbances and confirmed the paramount role of global warming in recent changes for daily gridded rainfall data .…”
Section: Studies Of Extreme Rainfall Trends In Indiasupporting
confidence: 79%
“…They have reported that in spite of considerable year-to-year variability, there are significant increases in the frequency and the intensity of extreme monsoon rain events in central India over the past 50 years and the observed trends suggest enhanced risks associated with extreme rainfall over India in the coming decades. The findings of Ghosh et al 23,24 were similar to those of Goswami et al 19 . Lacombe and McCartney 25 found changes in rainfall pattern aligning with the geography of anthropogenic atmospheric disturbances and confirmed the paramount role of global warming in recent changes for daily gridded rainfall data .…”
Section: Studies Of Extreme Rainfall Trends In Indiasupporting
confidence: 79%
“…While validating their 2006 study, Ghosh et al (2012) indicated increasing spatial variability in observed Indian rainfall extremes. They also found that moderate rainfall increased in central India despite a decreasing trend in occurrence of moderate rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the percentile-based method were widely used in many regions over the world because of its efficiency and simplicity (Bell et al, 2004;Wang and Zhou, 2005;Du et al, 2013). In most cases, the EP was based on the 90th (Gemmer et al, 2011), 95th (Bell et al, 2004;Zhai et al, 2005), 97.5th (Wang and Zhou, 2005) or 99th (Gemmer et al, 2011) percentiles of daily precipitation data, which represent moderate to extremely unusual events and were demonstrated to be appropriate in various regions (Alexander et al, 2006;Ghosh et al, 2012;Vittal et al, 2013). Three indicators, i.e., frequency (F), intensity (I) and extreme volume (EV), are often used to describe the characteristics and detect the trends of EP.…”
mentioning
confidence: 99%
“…However, the functional relationships between parameters and the time need to be specified as a priori, and such information might not be available or persistent over time due to the complexity of climate system (Kao and Ganguly, 2011;Ghosh et al, 2012). Alternatively, the distributional parameters were estimated separately for a series of Y-years moving window, rather than for the entire extreme series (Kao and Ganguly, 2011;Ghosh et al, 2012;Vittal et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation